A histochemical comparison of the O-acylated sialic acids of the epithelial mucins in ulcerative colitis, Crohn's disease, and normal controls. - Culling, C F (1979)
Two histochemical techniques, the PAT/KOH/PAS and the PBT/KOH/PAS, were used to investigate the side chain O-acyl substitution patterns of the sialic acids of the colonic epithelial mucins in cases of ulcerative colitis and Crohn's disease. In both diseases there was, as compared to normal, a reduction in the proportion of sialic acids O-acylated at C7C8, the reduction being greater in ulcerative colitis. Further, there appeared to be an association between the severity of the disease and the reduction in the staining of O-acylated sialic acids. This relationship was more marked in ulcerative colitis. In some cases of both diseases there was evidence for epithelial mucins containing predominantly C7-substituted sialic acids. This study has confirmed our previous conclusion that, in Crohn's disease of the terminal ileum, the disease is associated with an increase in the proportion of sialic acids bearing side chain substituents.